2000
DOI: 10.1023/a:1009591407163
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to determine the tuberculin positivity rates and the incidence of sexually transmitted diseases (STDs) among a population of seasonal, nonmigrating farm workers. Participants were tested for tuberculosis (TB) sensitivity, syphilis, gonorrhea, and chlamydia. Patients were afforded follow-up even if they returned home to Mexico during the course of their treatment. We found that the TB rate (15%) and the incidence of STDs to be significantly lower than in other studies of migrant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…A TB study conducted on migrant farm workers in Pennsylvania indicated that out 509 workers from 15 migrant camps who were tested for TB, 14.8% had a positive TB reaction [31]. Most of the subjects in this study were Mexicans (77%), and 13% of this subgroup tested positive for TB.…”
Section: Tuberculosis and Migrant Farmworkers Literature Reviewmentioning
confidence: 60%
See 1 more Smart Citation
“…A TB study conducted on migrant farm workers in Pennsylvania indicated that out 509 workers from 15 migrant camps who were tested for TB, 14.8% had a positive TB reaction [31]. Most of the subjects in this study were Mexicans (77%), and 13% of this subgroup tested positive for TB.…”
Section: Tuberculosis and Migrant Farmworkers Literature Reviewmentioning
confidence: 60%
“…The GUAPA project was the first successful, binationally coordinated, epidemiological investigation initiated between the Pennsylvania Department of Health and the Instituto Nacional de Salud Publica of Mexico [31]. The project was supported by the CDC and the Health and Human Services of Minority Health, which assured that Mexican patients were afforded follow-up and medical treatment for TB even if they returned home to Mexico during the course of their treatment.…”
Section: Guapa Projectmentioning
confidence: 99%